Effect of Wood Acetylation with Vinyl Acetate and Acetic Anhydride on the Properties of Wood-Plastic Composites - Nilgül Özmen; Nihat Sami Çetin; Fatih Mengeloğlu; Emre Birinci; Kadir Karakuş (BioResources, 2012)
Chemical modifications of Scots pine (Pinus slyvestris) wood flour were performed with vinyl acetate (VA) and acetic anhydride (AA) in the presence of potassium carbonate as a catalyst. Scots pine wood flour samples were successfully acetylated with VA (19 wt% gain) and AA (24 wt% gain). The effect of chemical modification of the Scots pine wood flour with AA and VA on the mechanical properties of wood high-density polyethylene composites (WPC) were determined. It was observed that acetylation of wood flour allowed a significant increase in both the mechanical properties and the thermal stability of the WPCs. It was concluded that acetylation of lignocellulosic fibers improves thermal stability, dispersion in the polymer matrix, and compatibility with the polymer matrix.
Keywords: Acetic anhydrides; Vinyl acetate; Scots pine; Wood plastic composites; TP248.13-248.65; Biotechnology; 3. Good health